Die Kultur der Klöster - Callori di Vignale, Christina; Grégoire, Reginald; Moulin, Léo; Oursel, Raymond; Callori di Vignale, Christina; Raave, Andreas (Belser, 1995)
Bildtextband über das Gemeinschafts- und Geistesleben sowie die kulturelle Bedeutung